Leadership in the mobile smartphone market - Reis Santos Mata, Flavia (My University, 2012)
The mobile telecommunications industry has been going through an enormous revolution, especially after mid-1990 when smartphones were introduced to the market. As a consequence, the smartphone market’s dynamism is requesting companies to operate differently in the way they do business. After a long period occupying the leader position in the smartphones manufacturers’ rank, Nokia was outperformed by Apple and Samsung during 2011 and since then has been on the third place. Nevertheless, Nokia is battling for regaining the leadership in such a competitive and high-velocity growing market and that is what this research is about. This research covers the competitive and strategic forces that shape dynamic industries whereas the main purpose is to elucidate the main factors that contribute to a company’s above-average performance and ultimately determine its leadership in the mobile smartphone market. Therefore, this exploratory qualitative research was conducted as a desk research, which utilized various secondary sources of data in the knowledge area of strategic management such as theories about competitive advantages and dynamic capabilities of firms, innovation, and strategy. This research is enriched with a case study about Nokia: how the company has been organizing its corporate structure to support the strategies and hence how it has been competing in the smartphone market is analyzed, taking into account many contemporary data sources, including market analysts’ and business experts’ opinions. As a result of the classic literature exploration and the case study assay, a framework for deeper analysis of the competitiveness of firms in dynamic markets was developed. The conclusion that emerged from this research is that the success of a firm results from the interplay of various factors. To regain the leader position in the mobile smartphone market is a challenging task that requires Nokia to reinvent its core strategy for taking charge of the smartphones’ industry transformation through for example the adoption of the open innovation concept. It is imperative that Nokia designs and implement a breakthrough strategy as well as embraces the uncertainty of the smartphone market competition as an opportunity for discontinuous innovation development with the ultimate goal of recovering the leadership.